A mass spectrometric method for rapidly assaying the chiral selectivities of the copper(I) complexes of C2‐symmetric ligands. (5th October 2015) - Davis, Mark C.; Gronert, Scott
Abstract : A gas‐phase method for rapidly assaying the enantioselectivity of metal‐centered catalysts is presented. It relies on gas‐phase equilibrium measurements in a quadrupole ion trap mass spectrometer. A group of well‐established C2 ‐symmetric bis‐oxazoline copper(I) complexes was used to identify chiral probe reagents that are capable of profiling the quality of the asymmetric environment provided by the metal complex. The chiral probes were then applied to a wide variety of copper(I) bis‐di‐imine complexes. Complexes based on a BINAM backbone exhibited selectivities that were comparable to the bis‐oxazolines. Taking advantage of the mass selectivity capabilities of the ion trap mass spectrometer, the method was also applied to an un‐purified mix of copper(I) complexes derived from a combinatorial synthesis of bis‐di‐imine ligands. This approach holds promise as a rapid screening tool for potential chiral catalysts. Copyright © 2015 John Wiley & Sons, Ltd.